ANALYSIS OF THE CAUSES OF LOW OIL RECOVERY - Nikolai Buktukov; Rustem Igizbaev; Gulnaz Moldabayeva; Evgenii Gumennikov; Elmira Yesbergenova (Rudarsko-geološko-naftni Zbornik)
This analytical review is aimed at identifying and analysing a variety of factors affecting the low oil recovery factor. The study covers a wide range of parameters, from the mining and geological conditions of deposits to the physical and mechanical properties of rocks and hydrocarbons. Attention is also paid to such important aspects as geological features, including fracturing of rocks, waterlogging of formations and folding of deposits, which can significantly complicate oil production. Statistical data on current oil recovery rates from different regions and countries were collected and analysed, which helped to identify the most common problems and typical oil recovery rates. The review highlights that, along with well-known factors such as high oil viscosity and low rock permeability, oil recovery factor is significantly influenced by resistance to extraction by gravity, and complex tectonic conditions such as the presence of folds and faults. In addition, the problems related to the modelling and representation of the oil reservoir are considered, which can lead to errors in the assessment of oil reserves and, consequently, to an underestimated oil recovery factor. In conclusion, the review suggests possible areas for the development of oil production technologies that can help to overcome the identified obstacles. Suggestions are given for improving methods of increasing oil recovery, such as the introduction of new technologies, improvement of existing methods, and conducting more accurate geological studies.